Penciptaan Karya Komposisi Penataan Gamelan Pelog - Salendro Untuk Aransemen Musik Sekolah - Cahyadi, Ojang (Program Studi Pendidikan Tari FBS UNJ, 2021)
Revealing arranged sounds through the composition of musical works is outlined in the arrangement of gamelan compositions for school music arrangements, motivated by the desire to provide alternative material and special gamelan playing techniques for school music arrangements, so that school students are interested in participating in gamelan learning. The sound in music is something that is alive and in the form of sounds that are arranged and have their own size, so that harmonious tones and rhythmic patterns are formed. The life of the sounds can be seen from the characteristics or character that are determined by the musical instruments, some sound by blowing, rubbing, tapping, hitting, and pressing. The sound of a musical instrument will merge with the soul of the musician as a musician's self-expression. A musician's work of art is an aesthetic experience and personal creative ideas that are incorporated into the work of music. The specific goals and objectives to be achieved in this research are to produce media products and teaching materials that are practical and make it easier for students to play the gamelan, and produce works of Sundanese gamelan arrangement compositions that are suitable as teaching materials. While the methodology in this research is qualitative which produces a product in the form of a Sundanese pelog salendro gamelan arrangement that has the legality of intellectual property rights and sheet music documentation or arrangement composition notation resulting from the research process of this artwork.